2020
DOI: 10.1017/s1368980020002992
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative evaluation of a social media campaign to improve healthy food habits among urban adolescent females in Indonesia

Abstract: Objective: The current study focuses on how adolescent girls in urban Indonesia accept technology in a social media (SM) campaign to promote healthy eating habits. Design: The study was a qualitative evaluation of the online campaign. In-depth interviews using semi-structured interview guidelines and focus group discussions were used to collect data. Data were analysed using a general inductive approach to provide simple and straightforward answers to our study questions. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 38 publications
(58 reference statements)
0
32
0
Order By: Relevance
“…The secondary school curriculum in Zambia offers some nutritional education as evidenced by 65% of school-going adolescents who reported having been taught about healthy eating and benefits of consuming fruit and vegetable [ 52 ]. School based lessons must be reinforced by social media communication campaigns tailored to adolescents, as these have been shown to improve healthy food habits among adolescents in countries like Indonesia [ 87 , 88 ]. Communication campaigns provide an opportunity to address concerns about affordability of healthy food by promoting consumption of locally available healthy foods that are relatively cheaper.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary school curriculum in Zambia offers some nutritional education as evidenced by 65% of school-going adolescents who reported having been taught about healthy eating and benefits of consuming fruit and vegetable [ 52 ]. School based lessons must be reinforced by social media communication campaigns tailored to adolescents, as these have been shown to improve healthy food habits among adolescents in countries like Indonesia [ 87 , 88 ]. Communication campaigns provide an opportunity to address concerns about affordability of healthy food by promoting consumption of locally available healthy foods that are relatively cheaper.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the findings of a recent Australian study, declaring a lack of healthy food options in high schools [ 26 ]. Earlier studies have emphasised the importance for future prevention programs to collaborate with stakeholders within the community (i.e., ME community) to provide environmental and interpersonal support [ 33 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This emphasises the importance of developing programs that encompass both delivery modes, social media and face-to-face, consistent with other findings [ 29 ]. This can be achieved by providing adolescents with information on social media from trustworthy sources, as well as organising face-to-face cooking classes, as reinforced in similar studies [ 29 , 37 ]. Despite respondents preferring school over community-based interventions, a previous systematic review has suggested that interventions are more effective if they involve schools and communities and/or families [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous study in Indonesia found that online campaign on Indonesian adolescent female was well accepted and motivated them to act the protective behavior. The health ministry needs to collaborate with influential person such as celebrity couple and other influential person to campaign about exclusive breastfeeding using social media that popular in Indonesian young women such as Instagram and Facebook [17].…”
Section: Discussionmentioning
confidence: 99%